The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1677/joe.0.1740127
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cyclo-oxigenase-2 activity does not abolish the anabolic effect of prostaglandin E2 in vivo or in vitro

Abstract: It was previously reported that the expression of cyclooxigenase-2 (COX-2) is induced by prostaglandin E 2 (PGE 2 ) in vitro in an osteogenic cell line and organ culture, suggesting an autoamplification mechanism. In this study, we first tested whether this phenomenon also occurs in bone tissue in vivo and found that a single anabolic dose of PGE 2 (5 mg/kg) induced (between 30 and 120 min) in rat tibiae, an increase in the mRNA level of COX-2 (2·5-to 9-fold) but not that of COX-1. Secondly, to test whether CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Interestingly there is a rise in PG levels in 15 and 45 days treatment groups this might be due to compensation by COX-1 for the loss of COX-2 or another isoform COX-3 that might have been involved (Chandrasekaran et al, 2002). It has also been reported that synthesis of PGs are independent of COX (Weinreb et al, 2002).…”
Section: Discussionmentioning
confidence: 89%
“…Interestingly there is a rise in PG levels in 15 and 45 days treatment groups this might be due to compensation by COX-1 for the loss of COX-2 or another isoform COX-3 that might have been involved (Chandrasekaran et al, 2002). It has also been reported that synthesis of PGs are independent of COX (Weinreb et al, 2002).…”
Section: Discussionmentioning
confidence: 89%
“…Since diabetes in vivo increases the apoptosis of mature osteoblasts (Motyl et al 2012), we hypothesized that the differentiation of cells due to DEX treatment might render them more sensitive to the apoptosis induced by AGE-BSA. BMSCs were treated with 10 nM DEX for 6 days (a regimen that we have repeatedly used to induce osteoblastic differentiation in rat BMSCs (Weinreb et al 2002(Weinreb et al , 2004) and then exposed to 400 mg/ml AGE-BSA for 16 h. Exposure to DEX, by itself, slightly increased the apoptosis of control cells (9 vs 6%); however, whereas AGE-BSA increased the apoptosis of BMSCs not treated with DEX about twofold, it increased apoptosis of DEXtreated BMSCs threefold (Fig. 4).…”
Section: Resultsmentioning
confidence: 99%
“…One explanation is that DEX treatment induces osteoblastic differentiation in BMSCs (evidenced by the acquirement of alkaline phosphatase activity and the production of mineralized extracellular matrix (Rickard et al 1994, Weinreb et al 2002) and by doing so renders them more sensitive to AGEs-induced apoptosis (Roszer 2011). This notion stems from the observations that diabetes increases the apoptosis of mature osteoblasts in vivo , Motyl et al 2012.…”
Section: Discussionmentioning
confidence: 99%
“…COX-1, but not COX-2, has been implicated in the regulation of the expression of the prostaglandin receptors in cervical carcinomas (18). On the other hand, inactivation of COX-2 has been reported to increase EP3 and EP4 receptor expression in a murine kidney cell line (19), although it failed to interfere with it in an osteogenic cell line (20). Nevertheless, the effects of mechanical stimuli and COX activity on the regulation of prostaglandin receptors in chondrocytic cells have yet to be examined.…”
Section: Cyclooxygenase (Cox)mentioning
confidence: 99%